2022
DOI: 10.1155/2022/3434383
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Toxicological Evaluation of Avicennia africana P: Beauv. (Avicenniaceae) Leaf Extract in a Rat Model

Abstract: Avicennia africana is an important ethnomedicinal plant that has long been used to treat malaria and several other diseases. Despite the plant’s antimalarial and other therapeutic properties, there is limited evidence-based data on its potential toxicity. Hence, the purpose of the current study was to assess the safety of A. africana leaf ethanolic extract (AAE). The study was designed to ascertain the cytotoxic effects of the crude extract on red blood cells (RBCs) as well as the acute and subacute toxicity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
(37 reference statements)
0
3
0
1
Order By: Relevance
“…In natural product-based pharmacotherapy research for infectious diseases, the plant extract may possess high therapeutic efcacy but could cause potential harm to cells or organs; hence, screening for toxicity of promising or lead compounds is crucial. Te current study evaluated the Advances in Pharmacological and Pharmaceutical Sciences AAE extracts were determined to be >100 µg/mL in this study, and they have negligible cytotoxic efects on red blood cells (RBCs) [60]. A similar outcome was obtained for artesunate (the positive control drug).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In natural product-based pharmacotherapy research for infectious diseases, the plant extract may possess high therapeutic efcacy but could cause potential harm to cells or organs; hence, screening for toxicity of promising or lead compounds is crucial. Te current study evaluated the Advances in Pharmacological and Pharmaceutical Sciences AAE extracts were determined to be >100 µg/mL in this study, and they have negligible cytotoxic efects on red blood cells (RBCs) [60]. A similar outcome was obtained for artesunate (the positive control drug).…”
Section: Discussionmentioning
confidence: 67%
“…This technique is based on the viable enzyme-mediated conversion of the yellowish tetrazolium to a purple compound (formazan) after reacting extracts with uninfected human erythrocytes. The CC 50 values of AAA, AAQ, and AAE extracts were determined to be >100 µ g/mL in this study, and they have negligible cytotoxic effects on red blood cells (RBCs) [ 60 ]. A similar outcome was obtained for artesunate (the positive control drug).…”
Section: Discussionmentioning
confidence: 99%
“…Figura 3: Média ± DP dos valores em % referente a taxa de viabilidade celular em células de Hepatocarcinoma HUH7 nos diferentes tempos de avaliação (24, 48 e 72 h). Comprovada a presença dos compostos fenólicos e flavonoides, foi analisada a viabilidade celular in vitro do EAG para validação inicial da ausência de citotoxicidade em células saudáveis (AHMED et al, 2022;GASPARINI et al, 2017;MAKIA et al, 2022;STEFANOWICZ-HAJDUK et al, 2022) Medjakovic et al, 2016).…”
Section: Triagem Fitoquímicaunclassified
“…Avecinnia africana, also known as black mangrove, has been shown to have various signi cant ethnomedicinal properties (Thatoi et al, 2016 andAhmed et al, 2022a). In our earlier study, we found that the ethanolic crude leaf extract of A. africana (AAE) had good antimalarial effects (Ahmed et al, 2022b).…”
Section: Introductionmentioning
confidence: 97%